2019
DOI: 10.1021/acs.langmuir.9b02621
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of Lyotropic Liquid-Crystal Phases—The Interplay between Liquid Crystalline Order and Physical Gel Formation

Abstract: We present a systematical investigation of gelled lyotropic liquid crystals (LLCs). This new class of soft materials combines the anisotropy of LLCs with the mechanical stability of a physical gel. The studied LLC system consists of sodium dodecyl sulfate as a surfactant, n-decanol as a cosurfactant, and water as a solvent. At room temperature, four liquid crystalline phases (lamellar Lα, nematic Nd and Nc, and hexagonal H1) are formed depending on the composition. We were successful in gelling the lyotropic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 99 publications
1
21
0
Order By: Relevance
“…The hydrogels formed by the SMG method showed higher cgc and lower T S-G and viscoelasticity values than those of the organogels. The hydrogel cgc values were much higher than that of the organogel obtained from 12-HOA and n-dodecane, which is approximately 0.2 wt.% [34]. The cgc increases with increasing solvent polarity and hydrogen-bonding ability of the solvent [13]; therefore, it seems reasonable that the cgc of a hydrogel is larger than that of the organogel.…”
Section: Discussionmentioning
confidence: 79%
“…The hydrogels formed by the SMG method showed higher cgc and lower T S-G and viscoelasticity values than those of the organogels. The hydrogel cgc values were much higher than that of the organogel obtained from 12-HOA and n-dodecane, which is approximately 0.2 wt.% [34]. The cgc increases with increasing solvent polarity and hydrogen-bonding ability of the solvent [13]; therefore, it seems reasonable that the cgc of a hydrogel is larger than that of the organogel.…”
Section: Discussionmentioning
confidence: 79%
“…As the temperature decreases, twisted ribbons are progressively formed in water, slowly leading to a 3D network of entangled fibers and finally a stable hydrogel after 3 days of equilibration at room temperature. This growth in the water phase was made possible because the elementary brick of 12-HOA was formed in the oil phase, 45 and because its subsequent assemblies were not disturbed in the presence of water.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of different self-assembled structures formed inside the same system is not unique, and many examples exist in nature or have already been formulated. [43][44][45][46][47][48][49][50] Gelled microemulsions have been described, leading to the coexistence of a water-in-oil microemulsion with a gelatin network, 22,23 or a bicontinuous microemulsion with a self-assembly of 12-HOA. 24 The latter may be considered as a particular organogel in which the gelled solvent is the bicontinuous phase of the microemulsion.…”
Section: Gelation Of the Nanoemulsionmentioning
confidence: 99%
“…[34,35] In recent years few studies on LLC gels as a new kind of LC networks were presented. [36][37][38][39][40] It was shown that the anisotropic order of the surfactant-based LLCs is combined with the mechanical stability and elasticity of a 3D physical gel network. Lyotropic lamellar and hexagonal phases were successfully gelled by LMWGs, but so far no lyotropic nematic physical gel was obtained.…”
Section: Doi: 101002/adma202007340mentioning
confidence: 99%
“…In a former paper we showed that lyotropic nematic physical gels are not as easily achievable as lamellar gels since the used gelator 12-HOA acts partly as cosurfactant and thus gelation of nematic LLCs with 12-HOA lead to lamellar gels only. [40] In this paper we restrict the term lyotropic nematic gels to the genuine nematic LLC phases formed by rod-or disk-like micelles and gelled by a fibrillar network. Please note that the term lyotropic nematic gel is also used in other contexts where the building blocks of the nematic phase are interacting with each other so that they form a gel network.…”
Section: Doi: 101002/adma202007340mentioning
confidence: 99%